Australian Journal of Environmental Education - Australian Journal of Environmental Education (Cambridge University Press, 2026)
The Australian Journal of Environmental Education (AJEE) is one of the oldest internationally refereed environmental education journals which publishes manuscripts on all aspects of contemporary research and practice. AJEE provides significant, innovative contributions to research and practice to communicate and stimulate debate for enhancing and expanding the field of environmental education. AJEE is Gold Open Access and is supported by an international Editorial Executive and Editorial Board.
FI 0.92
Q1
Keywords: Earth; Space & Environmental Sciences; Conservation; Acuerdos transformativos; Transformative agreements; Educación ambiental; Formación ambiental; Comunicación científica